MUSLIM COMMUNITY IN GERMANY: CURRENT CHALLENGES AND OPPORTUNITIES - Meirison Meirison; Darni Yusna (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2021)
A recent study showed that the number of Muslims had increased significantly in Germany since 2015. Many of them still face challenges in terms of employment and training. Religion may be a secondary cause of these challenges, "but it does not hinder integration in general." "We will do that," was the most famous phrase of German Chancellor Angela Merkel, in 2015, referring to her that her country is capable and ready to receive a large number of refugees, when Germany opened its doors to them and received about one million people, most of them from the Middle East, especially Syria. The author conducted a literature study by quoting from various sources as well as using a descriptive and comparative analysis approach, after about six years, the number of Muslims in Germany has become much larger, and the demographic structure has become less homogeneous, according to a recent official study, conducted by the Federal Office for Migration and Refugees (PAMF) at the request of the Islam Conference in Germany and the Federal Ministry of the Interior. However, the growing number of Muslims in Germany came under pressure as their numbers grew. Sometimes due to hatred and incitement from outside and within Germany itself. Cultural differences, especially religion, have become a catalyst for the emergence of such hatred. The number of Muslims continues to increase in line with the increasing efforts in cultural assimilation and the ongoing adjustment of the social environment that has changed the situation, which is expected to be better than the previous situation.